Mi'kmaq materials, Frank G. Speck Papers - Speck, Frank G. (Frank Gouldsmith), 1881-1950; Butler, Eva L.; Mechling, William Hubbs, 1888-1953 (1909)
Materials relating to Mi'kmaq history, language, and culture. Includes Speck's field notes on topics such as wampum, hunting territories, Cape Breton texts, Newfoundland traditions, the Passamaquoddy, etc., as well as a map with names of Bear River Band members and one piece of birch bark with pictographs inscribed; Speck's miscellaneous notes and correspondence on topics such as consultants, specimens, hieroglyphics, linguistics, fieldwork, Mi'kmaq and Cherokee, and the Mi'kmaq mission newspaper; a text on Mi'kmaq dance with interlinear translation, notes, and a musical score; 10 pages of linguistic notes and vocabulary collected along the Miramichi River, along with 6 pages of typed copy by John Witthoft; correspondence with Mechling concerning linguistic research on the Mi'kmaq, Malecite [Malecite-Passamaquoddy], and Oaxaca languages, Mi'kmaq burials, and historic materials on Beothuk and Mi'kmaq; a brief article on a traveler's account of the Mi'kmaq in 1822; an incomplete article or set of reading excerpts taken after 1922 by Speck from John G. Millais (1907); and extracts concerning the sweat house taken by Butler from the Jesuit Relations.